A comparison between Plato and Zoroaster : aspects of the philosophy in the Timaeus and the Gathas - Viviers, D. S. (Daniele Siobhan) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2001.